Advanced stimuli-responsive polymer nanocapsules with enhanced capabilities for payloads delivery. Issue 23 (21st June 2015) - Zhao, Yi; Lv, Li-Ping; Jiang, Shuai; Landfester, Katharina; Crespy, Daniel
<x xml:space="preserve">Abstract</x> Recent progress in the design, preparation, and application of stimuli-responsive polymer nanocapsules with enhanced capabilities for payloads delivery are reviewed.